SOCIAL PROJECTS AS A MECHANISM FOR THE INVOLVEMENT OF YOUTH IN PUBLIC ACTIVITY - A. Bakanach (Вестник университета)
The article discusses how young people as a social group. Its social activity is defined as participation in social practices. The analysis of existing youth organizations. On the example of the case - social project "UNION - Heirs of the Victory" is considered as the International Friendship Youth training mechanism